Measuring the prevalence and factors determining depression among adolescents and young adults in Nigeria - Ede, Moses Onyemaechi (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2025)
Purpose – This study measures the prevalence of depression and the factors that determine it among adolescents and young adults in Nsukka Local Government Area, Enugu State. Method – Six research questions and six null hypotheses guided the study. The design of the study was a descriptive survey design. A sample size of 150 adolescents and 150 young adults participated in the study. Three instruments were used to generate data. Mean and Standard Deviation were used to answer the research questions, while the t-test was used to test the null hypotheses at the .005 level of significance. Result – Findings of the study revealed that the prevalence of depression among adolescents are in existence as well as the prevalence of depression among young adults. Additionally, the findings also showed that the extent to which psychological, biological, and environmental factors contribute to depression among adolescents and young adults are high, while the symptoms of depression experienced by adolescents and young adults are positive. Implication – Some recommendations were made which include among others that: awareness programs should be implemented by governments and counsellors to help adolescents and young adults develop resilience skills to cope with environmental stressors, schools should provide training for teachers and staff members to recognize the signs of depression and offer appropriate support to students, governments should allocate resources to expand access to mental health services for adolescents and young adults, including increasing the availability of counselling services in schools. Originality/Value – This research is a research that discusses the measuring the prevalence and factors determining depression among adolescents and young adults. *** Tujuan – Studi ini mengukur prevalensi depresi dan faktor-faktor yang mempengaruhinya di kalangan remaja dan dewasa muda di Wilayah Pemerintahan Lokal Nsukka, Negara Bagian Enugu. Metode – Enam pertanyaan penelitian dan enam hipotesis nol menjadi panduan dalam penelitian ini. Desain penelitian menggunakan desain survei deskriptif. Sebanyak 150 remaja dan 150 dewasa muda berpartisipasi dalam penelitian ini. Tiga instrumen digunakan untuk mengumpulkan data. Rata-rata dan Simpangan Baku digunakan untuk menjawab pertanyaan penelitian, sementara uji t digunakan untuk menguji hipotesis nol pada tingkat signifikansi 0,005. Hasil – Temuan penelitian menunjukkan bahwa prevalensi depresi di kalangan remaja dan dewasa muda memang ada. Selain itu, temuan juga menunjukkan bahwa kontribusi faktor psikologis, biologis, dan lingkungan terhadap depresi di kalangan remaja dan dewasa muda cukup tinggi, sementara gejala depresi yang dialami oleh remaja dan dewasa muda bersifat positif. Implikasi – beberapa rekomendasi diajukan, di antaranya: program kesadaran harus dilaksanakan oleh pemerintah dan konselor untuk membantu remaja dan dewasa muda mengembangkan keterampilan ketahanan dalam menghadapi stresor lingkungan, sekolah harus memberikan pelatihan bagi guru dan staf untuk mengenali tanda-tanda depresi dan memberikan dukungan yang sesuai kepada siswa, pemerintah harus mengalokasikan sumber daya untuk memperluas akses layanan kesehatan mental bagi remaja dan dewasa muda, termasuk meningkatkan ketersediaan layanan konseling di sekolah. Orisinalitas/Nilai – Penelitian ini merupakan penelitian yang membahas pengukuran prevalensi dan faktor-faktor yang menentukan depresi di kalangan remaja dan dewasa muda.